32+b2=62

Raise 3 to the power of 2.

9+b2=62

Raise 6 to the power of 2.

9+b2=36

Subtract 9 from both sides of the equation.

b2=36-9

Subtract 9 from 36.

b2=27

b2=27

Take the square root of both sides of the equation to eliminate the exponent on the left side.

b=±27

Simplify the right side of the equation.

Rewrite 27 as 32⋅3.

Factor 9 out of 27.

b=±9(3)

Rewrite 9 as 32.

b=±32⋅3

b=±32⋅3

Pull terms out from under the radical.

b=±33

b=±33

The complete solution is the result of both the positive and negative portions of the solution.

First, use the positive value of the ± to find the first solution.

b=33

Next, use the negative value of the ± to find the second solution.

b=-33

The complete solution is the result of both the positive and negative portions of the solution.

b=33,-33

b=33,-33

b=33,-33

The result can be shown in multiple forms.

Exact Form:

b=33,-33

Decimal Form:

b=5.19615242…,-5.19615242…

Solve for b 3^2+b^2=6^2